Myanmar's Trade and its Potential - Benno Ferrarini (Asian Development Bank (ADB), 2013)
The paper tabulates Myanmar's merchandise trade as reported by its partner countries, thereby circumventing the data constraints stemming from Myanmar's patchy trade records. It then estimates Myanmar's export potential, based on the bilateral export patterns observed for six other countries in Southeast Asia. Against that benchmark and controlling for outliers, Myanmar is found to be trading at about 15% its potential. The bulk of this gap is explained by very low trade with the industrialized countries. Through reintegration with the world economy accompanied by deep economic reforms domestically, Myanmar would be expected to be closing this gap rather swiftly.
hdl:11540/2084
Keywords: F14; F17; 330; Myanmar; gravity model; export potential; Außenhandel; Gravitationsmodell; Schätzung; Myanmar